Critical Analysis of Orientalist Understanding of Polygamy Sharia - Alfian, Muhammad; Purwanto, Muhammad Roy (International Journal of Science and Society, 2024)
Polygamy is a term that contains various meanings, often exciting men's imaginations as an ideal while triggering deep emotions in women. Many women, naturally jealous and reluctant to share their husband's love, oppose polygamy. Despite this, some extraordinary women accept it patiently. On one side, critics link polygamy to gender inequality and discrimination against women, while supporters believe it can reduce infidelity and prostitution. Misconceptions about polygamy, often fueled by anti-Islamic sentiment, have influenced Muslim society, leading some to view it negatively and others to defend it as a part of Islamic perfection. This research then aims to find out how orientalists criticize polygamy law and refute orientalist understanding of polygamy law. This research method will be carried out using a qualitative approach. The data used in this research comes from the results of a literature study of previous literature and research that is still relevant. The results of this research then found that the polygamy law in Islam has a strong historical basis, aiming to protect and regulate the practice of polygamy with the principles of justice and responsibility. Islam sets strict limits and conditions to ensure that polygamy is not abused and that women's rights are protected. Misinterpretations by Orientalists often ignore this context and spread biased views regarding polygamy law. Despite challenges and criticism of the practice of polygamy, education and fair enforcement of the law can provide significant social and individual benefits.